The Carlyles - Von Ziegesar, Cecily (New York, NY : Little, Brown and Co., 2008)
Triplets Avery, Baby, and Owen Carlyle have different approaches to their new life in a Manhattan penthouse and elite private schools, but soon each has cause to want to return to their home on Nantucket Island.
"Poppy."
Keywords: Interpersonal relations -- Fiction; Triplets -- Fiction; Brothers and sisters -- Fiction; High schools -- Fiction; Wealth -- Fiction; Schools -- Fiction; New York (N.Y.) -- Fiction